Community Empowerment in Preventing Criminal Actions of Corruption in Sibetan Village, Bebandem District, Karangasem Regency - I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara; Ni Kadek Erika; Putu Anggelita Putri; Kadek Darmayanti Putri (Community Service Journal of Law, 2022)
The rise of corruption cases that occurred at the Village Credit Institution in Bali made the Sibetan village community worried, the same thing would happen in the Village Credit Institution of the Sibetan Traditional Village. Starting from that, community leaders of the Sibetan traditional village in collaboration with the Law Society of Warmadewa University organized cooperation in increasing public awareness. The study aim is to minimize corruption that is still found in Bali. Bali is famous for upholding a culture of law and order with the teachings of karma phala, it is means that whoever does the deed will receive the consequences of their actions. This happens because of a lack of knowledge about the law, especially corruption. The researcher used an empirical service method with the approach of local traditional institutions, in service to the field of corruption knowledge related to the rampant corruption in the Village Credit Institution in preventing corruption cases in the Village Credit Institution of Sibetan. The results show that there is a warm discussion in addressing corruption cases in Bali so that in the future it will not happen in the Sibetan Traditional Village.